ANTIBACTERIAL EFFECTIVITY OF KASTURI LEAF EXTRACT (Mangifera casturi) AGAINST THE GROWTH OF Streptococcus sanguinis BACTERIA - Dita Puspita Sari; Didit Aspriyanto; Irham Taufiqurrahman (FKG Unlam, 2020)
Background: Caries is a disease that occurs because of the fermentation carbohydrates process by microorganisms in the oral cavity. One of the bacteria that causes caries is Streptococcus sanguinis. These bacteria will colonize on the tooth surface, then form dental plaques and contribute to the causes of caries and other periodontal diseases. Kasturi leaf extract (Mangifera casturi) has various compounds such as tannins, terpenoids, alkaloids, and flavonoids that have antimicrobial substances. Purpose: The aim of this study was to determine antibacterial effectivity of kasturi leaf extract (Mangifera casturi) against the growth of Streptococcus sanguinis bacteria. Method: This research was an experimental method laboratory (true experimental), with a randomized pre test and post test with control group design using 5 treatments: kasturi leaf extract (concentration: 20 mg/ml, 25 mg/ml, and 30 mg/ml); and two groups of control: positive control and negative control. Each treatment was repeated 5 times. Antibacterial activity testing used a liquid dilution method. Measurement of minimum inhibitory concentration (MIC) used a Uv-Vis Spectrophotometer and measurement of the minimum bactericidal concentration (MBC) used a colony counter. The MIC data were analyzed using One Way Anova and continued with the Dunnet Post Hoc test. MBC data were analyzed using the Kruskal-Wallis test and continued with the Mann-Whitney Post Hoc test. Result: One-Way Anova test showed that MIC had a significant difference, and the Kruskal-Wallis test showed that MBC also had significant differences. MIC was obtained at the concentration of 20 mg/ml and MBC was obtained at the concentration of 30 mg / ml. Conclusion: There is antibacterial effectiveness in kasturi leaf extract (Mangifera casturi) against the growth of Streptococcus sanguinis.